PENINGKATAN KETERAMPILAN SOSIAL DALAM KERJA KELOMPOK DENGAN PEMBELAJARAN OUTDOOR STUDY - Mulat Sudrajat; Pargito Pargito; Risma. M Sinaga (Jurnal Studi Sosial / Journal of Social Studies, 2015)
This study aimed to improve social skills in group work and social studies with outdoor study. The research methodology used Classroom Action Research Approach. The results showed that study of outdoor learning can improve social skills in group work, Cycle III of social skills in work groups of students for each indicator was visible on the indicator of turns or share a very good criteria with a total score of 109, or 90.83%, both indicators provide criticism and suggestions gained both criteria with a total score of 104, or 86.66%, The third indicator of emotional control criteria obtained a very good total score of 96 or 80%, obtained good the fourth indicator criteria very well with a total score of 91 or 50.83%, the fifth indicator of expressing opinion in problem solving obtained criteria with a total score of 82 or 63.33%, The sixth indicator receive opinions find solutions together to get both criteria with a total score of 84 or 70%.Penelitian ini bertujuan untuk meningkatkan keterampilan sosial dalam kerja kelompok mata pelajaran IPS dengan outdoor study. Metodologi penelitian ini menggunakan pendekatan Penelitian Tindakan Kelas. Hasil penelitian menunjukkan pembelajaran outdoor study dapat meningkatkan keterampilan sosial dalam kerja kelompok. Pada akhir siklus III keterampilan sosial dalam kerja kelompok setiap indikatornya terlihat pada indikator bergiliran atau berbagi memperoleh kriteria sangat baik dengan skor total 109 atau 90,83%, indikator memberikan kritik dan saran memperoleh kriteria baik dengan skor total 104 atau 86,66%, indikator mengontrol emosi memperoleh kriteria sangat baik skor total 96 atau 80%, indikator memperoleh kriteria sangat baik dengan skor total 91 atau 50,83%, indikator menyampaikan pendapat pemecahan masalah memperoleh kriteria baik dengan total skor 82 atau 63,33%, indikator menerima pendapat mencari solusi bersama mendapatkan kriteria baik dengan skor total 84 atau 70%.Kata kunci: kerja kelompok, keterampilan sosial, outdoor study